PENERAPAN METODE ACTIVE LEARNING DALAM MENINGKATKAN HASIL BELAJAR DI SMPN 5 ENREKANG - Fitrayani Shultan; Andi Bunyamin; Surani; Syarifa Raehana; Ahmad Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Finding out how the use of active learning techniques might enhance student learning outcomes in Islamic Religious Education (PAI) classes in class VIII B at SMP Negeri 5 Enrekang was the aim of this study. The low degree of student participation in the learning process and learning results that did not meet the minimal completion requirements served as the impetus for this investigation. A two-cycle Classroom Action Research (CAR) methodology is used in this study. The phases of planning, carrying out, observing, and reflecting are all included in each cycle. Learning outcome exams (10-item multiple-choice initial tests), documentation, interviews with Islamic Religious Education (PAI) teachers, and observation were used to gather data. 28 pupils from SMP Negeri 5 Enrekang's class VIII B (17 boys and 11 girls) served as the study's subjects. The study's findings demonstrated that student learning outcomes had increased. The average pre-test score of 65 (39.21%), post-test cycle I score of 76.42 (60.71%), and post-test cycle II score of 83.57 (85.71%) all demonstrate this. The effectiveness of the learning approach was demonstrated by this rise, which surpassed the success indicator (78).